A New Discovery of Argon Functioning in Plants: Regulation of Salinity Tolerance - Jun Wang; Chenxu Cai; Puze Geng; Feng Tan; Qing Yang; Ren Wang; Wenbiao Shen (MDPI AG, 2022)
Argon, a non-polar molecule, easily diffuses into deeper tissue and interacts with larger proteins, protein cavities, or even receptors. Some of the biological effects of argon, notably its activity as an antioxidant, have been revealed in animals. However, whether and how argon influences plant physiology remains elusive. Here, we provide the first report that argon can enable plants to cope with salinity toxicity. Considering the convenience of the application, argon gas was dissolved into water (argon-rich water (ARW)) to investigate the argon's functioning in phenotypes of alfalfa seed germination and seedling growth upon salinity stress. The biochemical evidence showed that NaCl-decreased α/β-amylase activities were abolished by the application of ARW. The qPCR experiments confirmed that ARW increased NHX1 (Na+/H+ antiporter) transcript and decreased SKOR (responsible for root-to-shoot translocation of K+) mRNA abundance, the latter of which could be used to explain the lower net K+ efflux and higher K accumulation. Subsequent results using non-invasive micro-test technology showed that the argon-intensified net Na+ efflux and its reduced Na accumulation resulted in a lower Na+/K+ ratio. NaCl-triggered redox imbalance and oxidative stress were impaired by ARW, as confirmed by histochemical and confocal analyses, and increased antioxidant defense was also detected. Combined with the pot experiments in a greenhouse, the above results clearly demonstrated that argon can enable plants to cope with salinity toxicity via reestablishing ion and redox homeostasis. To our knowledge, this is the first report to address the function of argon in plant physiology, and together these findings might open a new window for the study of argon biology in plant kingdoms.